Government auditing and its influences on the court of auditors of the state of Rondônia - Oliveira , Elaine Barbosa de Jesus; Souza , Naiara Meireles de; Rossoni , Estela Pitwak (Seven Editora, 2023)
The main objective of this work was to analyse the government audit process at the Rondônia State Court of Auditors (TCE/RO) and its influences. To this end, a bibliographical survey was carried out and, in addition, a literature review was constructed based on the reporting method for systematic reviews and meta-analysis (PRISMA). Thus, it was possible to observe that no work dealt with issues related to the government audit of the TCE/RO. Furthermore, the main conclusions were that the audit process at TCE/RO occurs through the planning, execution, reporting, and monitoring phases, following the premises of the audit procedures of the Federal Court of Auditors. Furthermore, it was found that the majority of advisors were chosen due to political influence, with 28.6% appointed by the state governor with approval from the legislative assembly and 71.4% appointed by the legislative assembly. DOI:https://doi.org/10.56238/sevened2023.006-077